(untitled) (Medical Forum Monthly, 2021)
Objective: To study the frequency and types of seizures among patients presenting with stroke. Study Design: Descriptive Cross-sectional study. Place and Duration of Study: This study was conducted at the Department of Medicine lady Reading Hospital Peshawar from January, 2020 to July, 2020 for a period of six months after approval of synopsis. Materials and Methods: Data was collected by non-probability consecutive sampling technique. A total of 177 patients were included in the study. Patients with acute ischemic stroke and haemorrhagic stroke both genders and 20 years and above age were included in the study. The major resultant outcome measures were the occurrence of single or recurrent seizures and the occurrence of both early (within 2 weeks) and late (after 2 weeks) seizures were noted. Those patients who already were having history of seizures, those with sub-arachnoid hemorrhage and also those with intra-cerebral bleed were excluded from the study. Data were analysed using SPSS version 23. Results: Among 177 patients, males were 96 (54.6%) and females were 81 (45.4%). The mean age was 63.47 ±11.62 years. Post stroke seizures were found in 33 (20.2%) patients with acute stroke. Among these, 16 (48.48%) were males and 17 (51.51%) were females, p value 0.276. Out of 177 patients 17(9.6%) had early seizures and 22 patients (12.4%) had late seizures. Conclusion: post stroke seizures were found with increased frequency in patients with acute stroke